STRATEGI PENYELESAIAN KONFLIK LAHAN OLEH PEMERINTAH DAERAH KABUPATEN KAMPAR ( Studi Kasus PT. Sekar Bumi Alam Lestari dengan Persatuan Koto Aman Menggugat (PEKAM) di Kecamatan Tapung Hilir ) - Martia Ningsih; Harapan Tua RFS (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Land has a high enough position in a country, especially for the community because it is an important asset that can be a source of life. Therefore, this often creates problems between several parties and causes conflicts. Such as the conflict between PT. Sekar Bumi Alam Lestari with the Persatuan Koto Aman Menggugat (PEKAM) in Tapung Hilir District, Kampar Regency. This study aims to determine the strategy for resolving land conflicts by the Kampar District Government and to determine the inhibiting factors. This study uses a descriptive qualitative method with a case study approach, where the determination of informants using purposive sampling technique. This study uses the theory of conflict resolution strategies from Stevenin in Hary Sucahyowati (2017), namely Introduction, Diagnosis, Agreeing on a Solution, Implementation, and Evaluation. The results show that the strategy of the Kampar district government in overcoming this land conflict has not been successful, and the inhibiting factor for the resolution of this land conflict is that the two parties in the conflict feel right and demand without evidence and grounds of rights. Keywords: Strategy, Conflict Resolution, Land Conflict.